Electrospinning preparation of oxygen-deficient nano TiO2-x/carbon fibre membrane as a self-standing high performance anode for Li-ion batteries. Issue 7 (12th July 2017) - Jing, Mao-xiang; Li, Jing-quan; Han, Chong; Yao, Shan-shan; Zhang, Ji; Zhai, Hong-ai; Chen, Li-li; Shen, Xiang-qian; Xiao, Ke-song
Abstract : Improving the specific capacity and electronic conductivity of TiO2 can boost its practical application as a promising anode material for lithium ion batteries. In this work, a three-dimensional networking oxygen-deficient nano TiO2-x /carbon fibre membrane was achieved by combining the electrospinning process with a hot-press sintering method and directly used as a self-standing anode. With the synergistic effects of three-dimensional conductive networks, surface oxygen deficiency, high specific surface area and high porosity, binder-free and self-standing structure, etc., the nano TiO2-x /carbon fibre membrane electrode displays a high electrochemical reaction kinetics and a high specific capacity. The reversible capacity could be jointly generated from porous carbon, full-lithiation of TiO2 and interfacial lithium storage. At a current density of 100 mA g −1, the reversible discharge capacity can reach 464 mA h g −1 . Even at 500 mA g −1, the discharge capacity still remains at 312 mA h g −1 . Compared with pure carbon fibre and TiO2 powder, the TiO2-x /C fibre membrane electrode also exhibits an excellent cycle performance with a discharge capacity of 209 mA h g −1 after 700 cycles at the current density of 300 mA g −1, and the coulombic efficiency always remains at approximately 100%.